2016
DOI: 10.1186/s12957-016-1034-y
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of combining denosumab and surgery in giant cell tumor of bone—a case series

Abstract: BackgroundThe RANK ligand inhibitor denosumab is being investigated for treatment of giant cell tumor of bone, but the available data in the literature remains sparse and controversial. This study analyzes the results of combining denosumab with surgical treatment and highlights possible changes for the oncologic surgeon in daily practice.MethodsA total of 91 patients were treated surgically for giant cell tumor of bone between 2010 and 2014 in an institution, whereas 25 patients of the total additionally rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 20 publications
6
74
0
7
Order By: Relevance
“…Several studies have reported the newly formed sclerotic bone and thickened cortex made it difficult to identify surgical margin and to curette. Residue tumor cells may hide within the new bone and thickened cortex and may recur once denosumab is discontinued [22,24,25].Traub et al [25] described that the tumor tissue was replaced by gritty, fibrous-like tissue new bone, they suggested intra-operative fluoroscopy to guide the extent of resection. On the other hand, it is argued that the newly formed peripheral bone rim and hardened tumor tissue reduced the risk of inadvertent contamination [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the newly formed sclerotic bone and thickened cortex made it difficult to identify surgical margin and to curette. Residue tumor cells may hide within the new bone and thickened cortex and may recur once denosumab is discontinued [22,24,25].Traub et al [25] described that the tumor tissue was replaced by gritty, fibrous-like tissue new bone, they suggested intra-operative fluoroscopy to guide the extent of resection. On the other hand, it is argued that the newly formed peripheral bone rim and hardened tumor tissue reduced the risk of inadvertent contamination [19].…”
Section: Discussionmentioning
confidence: 99%
“…Müller et al have focused on benefits and risks of D-mab treatment of GCTB 7. A total of 18 patients were treated with D-mab preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab kitle çevresinde periferik bir rim oluşturarak, intraoperatif kanamayı azaltarak ve kitlenin derecesini agresiften aktif veya latent hastalığa çevirerek cerrah için önemli bir yardım oluşturur (37). Denosumab tedavisi mikrovasküler yoğunluğu azaltarak intraoperatif kanamayı azaltır (37).…”
Section: Denosumab Etki Mekanizmasıunclassified
“…Denosumab periferik bir rim oluşturarak ve aşamayı agresiften aktif veya latent hastalığa çevirerek onkolojik cerraha yardımcı olabilir. Canlı tümör hücrelerinin kalması nedeniyle akut tedavi edilebilen bir hastalığının kronik bir hastalığa çevirebilir (37,42). Denosumab tedavisinden sonra gelişen septaların duvarında canlı hücreler kalabilir tümör hücreleri yeni oluşan kemikte kaldığından dolayı küretajın cerrahi tekniği, daha yüksek lokal nüks oranları önlemek için daha agresif olarak uygulanmalıdır (37).…”
Section: Denosumab Tedavisi Sonrası Dev Hücreli Tümörde Tekrarlamaunclassified
See 1 more Smart Citation